Indonesia Marine Debris: Banda Aceh Coastal Environment Identification - Koko Ondara; Ruzana Dhiauddin (Universitas Diponegoro, 2020)
Banda Aceh City, having an area of 61.36 km² with a coastline of 11 km which covers Ulee Lheu Beach to Alue Naga Beach. The research was carried out to determine marine debris statistics (type, amount and mass) which divided into 7 categories; plastic, metal, glass, rubber, processed wood (organic), clothing, and ceramics. This research also conducted to complement the Indonesian marine debris data which currently incomplete. We choose Banda Aceh as the preliminary location because its area affected by dynamic oceanographic parameters of the Indian Ocean, Bay of Bengal and bordered by several countries that could be a source of marine debris, thus making this research is important to do. Marine debris data were collected from March to May 2019, on the coast and waters surface. Data collection on the beach is carried out every 28 days using the transect method, while on the water surface by riding boats using visual observation techniques. Statistical results show that inorganic litter has the highest percentage and mass, which a mass density reached 288.37 g/100 m2 at Ulee Lheu Beach and 64.96 g/1 00 m2 at Alue Naga Beach. Plastic type dominates the type of marine debris on the beach about 92.2% and 51.4% on the water surface. The amount of plastic especially bottle continues to accumulate, it will not only endanger marine waters ecosystem but also potential to affect and damage the coastal environment. The results of this study are expected to provide input / recommendations for the government and related institutions in waste management in coastal and marine areas and tourism in a sustainable and sustainable way.